2015
DOI: 10.1074/jbc.m114.631697
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycans Are Important for Islet Amyloid Formation and Islet Amyloid Polypeptide-induced Apoptosis

Abstract: Background: Islet amyloid causes ␤ cell death in T2D. Results: Overexpression of heparanase reduced islet amyloid formation in cultured islets, and cells lacking surface associated HS were protected against IAPP-mediated toxicity. Conclusion: IAPP fibrillation requires HSPG interaction for induction of apoptosis. Significance: Inhibition of the HS and hIAPP interaction poses a potential intervention target to prevent ␤ cell death in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 57 publications
(61 reference statements)
1
43
0
Order By: Relevance
“…Enzymatic removal of HSPG (Oskarsson et al 2015, Potter et al 2015 or blockade of HSPG binding sites (Hull et al 2007) reduced islet amyloid formation in hIAPP transgenic mouse or human islets in vitro; this suggests that the proteoglycans are a binding site for IAPP on the outside of the cell. If HSPGs are a primary anchoring site in the extracellular space for monomeric secreted hIAPP then hIAPP/HSPG interactions could lead to a high local concentration of hIAPP and promote aggregation (Westermark 1973).…”
Section: R132 Review D Raleigh and Othersmentioning
confidence: 99%
“…Enzymatic removal of HSPG (Oskarsson et al 2015, Potter et al 2015 or blockade of HSPG binding sites (Hull et al 2007) reduced islet amyloid formation in hIAPP transgenic mouse or human islets in vitro; this suggests that the proteoglycans are a binding site for IAPP on the outside of the cell. If HSPGs are a primary anchoring site in the extracellular space for monomeric secreted hIAPP then hIAPP/HSPG interactions could lead to a high local concentration of hIAPP and promote aggregation (Westermark 1973).…”
Section: R132 Review D Raleigh and Othersmentioning
confidence: 99%
“…Using cells and transgenic rodents as disease models, other studies found hIAPP fibrils to be associated with apoptosis, β-cell loss, and T2D severity (O'Brien et al, 1995; Hiddinga and Eberhardt, 1999; Janson et al, 1996; Hull et al, 2005a, 2005b; Pilkington et al, 2016). In contrast, some studies show that the process of hIAPP fibril formation, not the amyloid fibrils themselves, is the source of toxicity (Schlamadinger and Miranker, 2014; Oskarsson et al, 2015). However, most current research studies suggest soluble pre-fibrillar oligomers are the primary type of toxic aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of cell surface GAGs did not reduce the vulnerability of CHO cells towards IAPP (De Carufel et al 2013). In contrast, isolated islets of double-transgenic mice overexpressing both heparinase and hIAPP had less amyloid deposition than the islets isolated from hIAPP transgenic mice (Oskarsson et al 2015). The relation between sulfated GAGs and amyloid-related cytotoxicity was also investigated with Aβ.…”
Section: Biological Relevance Of Gag-mediated Amyloid Assemblymentioning
confidence: 99%
“…Two of these structural models describe a monomer with a disordered N-terminal domain and two segments in β-sheet conformation, where each β-strand participates in two different parallel in-register β-sheets (Paravastu et al 2008;Petkova et al 2006). The two segments are linked by a loop and monomers are stack along the fibril axis.…”
Section: Molecular Architecture Of Amyloid Fibrilsmentioning
confidence: 99%